Intermediate financial theory - Danthine, Jean-Pierre (Academic Press advanced finance series., 2005)
The second edition of this authoritative textbook continues the tradition of providing clear and concise descriptions of the new and classic concepts in financial theory. The authors keep the theory accessible by requiring very little mathematical background. First edition published by Prentice-Hall in 2001- ISBN 0130174467. The second edition includes new structure emphasizing the distinction between the equilibrium and the arbitrage perspectives on valuation and pricing, as well as a new chapter on asset management for the long term investor."This book does admirably what it sets out to do -